Carbon Taxes Crowd Out Climate Concern: Experimental Evidence from Sustainable Consumer Choices - Alice Pizzo; Christina Gravert; Jan M. Bauer; Lucia Reisch (CESifo GmbH, 2025)
We examine the impact of a carbon tax on consumer choices via a large-scale online randomized controlled trial. Higher taxes generally reduce the demand for high-carbon goods. Compared to an import tax, a carbon tax reduces demand when the tax is zero (i.e., announced but not levied) but leads to relatively higher demand for high-carbon goods when a positive tax is introduced. This contradiction of basic price theory is entirely driven by climate-concerned consumers. Our findings suggest that carbon taxes can crowd out climate concerns, leading to important implications for policy.
Keywords: Q58; C90; d030; D90; Q50; Q51; 330; behavioral response; carbon pricing; climate change; climate policy; experiment; moral licensing